PENGARUH STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA PESERTA DIDIK KELAS IV SD NEGERI 11 LIMBOTO - Hidayana, Siti; Pateda, Lamsike; Rizki Pautina, Amalia (EDUCATOR (DIRECTORY OF ELEMENTARY EDUCATION JOURNAL), 2021)
This article aims to discuss the Influence of Directed Reading Thinking Activity Strategy on Reading Comprehension Ability in Fourth Grade Students’ of SD Negeri 11 Limboto. This strategy is used to determine whether there is an effect on the students' reading comprehension ability. This research uses quantitative research with a pre-experimental approach. The population in this research about 30 students’, and the sample was only 10 students’ who were included in the low category, so this research was said to be a purposive sampling study. Data collection uses tests (pretest and posttest), the data analysis used the normality analysis. The results of the research, founded that the Directed Reading Thinking Activity strategy had a significant effect on the reading comprehension ability of the fourth grade students of SD Negeri 11 Limboto, which 90.50% was obtained from the calculation results. And it can be seen from (2 tailed) = 0,00 < 0,05, this is indicates that H0 is rejected and H1 is accepted.